Pengolahan Jeruk Nipis untuk Peningkatan Nilai Tambah Produk Unggulan Desa Bolo, Kabupaten Gresik - Nina Lisanty; Djoko Rahardjo; Nur Laili Wahyu Triana; Roszana Wahyuniati (Kadiri University, 2022)
Bolo Village in Ujungpangkah District, Gresik Regency, East Java Province is well-known as a producer of good quality limes. Lime farming in the area has been proven to increase the income of farmers and the surrounding community. This potential requires more support to be used as a superior village product with added value for increasing farmers' income and community welfare. Community service activities were conducted at the location through training methods, especially community participatory, with the hope that the participants could implement the results of the training. The activities were carried out three times based on the products made from lime. The first training was the manufacture of hand sanitizer products, followed by training on making aromatherapy candles and instant powder drinks on another predetermined day. The participating communities had the opportunity to take home the products from the training as souvenirs as well as a reminder for them to apply the training activities by producing the three products. The Bolo Village community service activity in the future is faced with product development and quality, as well as assistance on the legality of community businesses.Â Desa Bolo di Kecamatan Ujungpangkah, Kabupaten Gresik, Provinsi Jawa Timur terkenal sebagai penghasil jeruk nipis berkualitas baik. Usahatani jeruk nipis terbukti dapat meningkatkan pendapatan petani dan masyarakat sekitar. Potensi ini memerlukan dukungan untuk dapat dijadikan produk unggulan desa dengan nilai tambah demi peningkatan pendapatan petani dan kesejahteraan masyarakat. Kegiatan pengabdian kepada masyarakat dilakukan di lokasi melalui metode pelatihan, terkhusus community participatory, dengan harapan masyarakat peserta dapat mengimplementasikan hasil pelatihan. Kegiatan pelatihan dilakukan dalam 3 waktu berdasarkan produk yang dihasilkan berbahan baku jeruk nipis. Pelatihan pertama adalah pembuatan produk hand sanitizer, dilanjutkan pelatihan pembuatan lilin aromatherapy dan minuman serbuk instan di hari lain yang telah ditentukan. Masyarakat peserta antusias dalam kegiatan pelatihan. Mereka berkesempatan membawa pulang produk hasil pelatihan sebagai cenderamata sekaligus pengingat bagi mereka untuk benar-benar mengaplikasikan kegiatan pelatihan dengan menghasilkan ketiga produk berbahan baku jeruk nipis tersebut. Kegiatan pengabdian masyarakat Desa Bolo ini untuk ke depannya dihadapkan pada pengembangan produk dan kualitasnya, serta pendampingan legalitas usaha masyarakat.